Ameliorative potentials of methanol leaf extract of Newbouldia laevis on monosodium glutamate induced toxicity in female albino rats - Itez, Paul; Aloh, S Godwin; Osuocha, Kelechi U.; Iwueke, Adaku V.; Chukwu, Ezinne C. (African Science Publications, 2020)
Newbouldia laevis is a valuable tropical plant belonging to the family of Bigoniaceae. The plant is believed by most herbal practitioners to be the tree of fertility and of immense medicinal benefits to humans. This study examined ameliorative potencies of Newbouldia laevis on monosodium glutamate induced toxicity in female albino rats for 14 days. Group A received 800 mg/kg body weight of Monosodium Glutamate (MSG), while Group B received 8,000 mg of MSG + 400 mg of extract. Group C received 8,000 mg of MSG and 600 mg of N. laevis. Group D received feed and water. Group E received 200 mg of extract and Group F received 8,000 mg of MSG. Results showed no significant difference (p > 0.05) in Aspartate Aminotransferase (AST), Alkaline Phosphatase (ALP) and Total Protein (TP) of rats exposed to MSG + extracts and MSG-alone. Significant (p < 0.05) elevation in Alanine Transferase (ALT) and serum albumin were recorded for rats exposed to MSG + 400 mg and 200 mg of extract. There was no significant difference in cholesterol level in rats exposed to MSG alone compared to other groups. Significant elevation in urea level occurred in rats exposed to 8,000 mg MSG + 600 mg of the extract, reduction occurred in those exposed to 8,000 mg MSG + 400 mg of the extract. Those exposed to normal saline and 200 mg of extract leveled up with rats exposed to MSG. Study indicates protection of liver architecture and ameliorating effect of N. laevis on MSG intoxication.
Keywords: Monosodium glutamate, Newbouldia laevis, Ameliorative, Potentials